Body Composition Assessment of Athletes Participated in Cyclic Sports - Rakhmatova Markhabo Rasulovna (Scholars Digest Publishing, 2023)
Changes in indicators of the body composition of athletes during physical exertion are closely interconnected with the functional indicators of systems that determine performance. One of the methods that determine the adequacy of physical activity is the determination of the component composition of body weight. Body composition parameters include body fat, lean mass, and skeletal mass, which are needed to compare the data of the athletes we study, which differ in age and physique.
Keywords: junior athletes and cadets, body composition, working capacity.